The Frequency of Integrons and OXA Genes in Uropathogenic Isolates of Klebsiella pneumoniae: Transmission of antimicrobial resistance in Klebsiella pneumoniae - Pourbaghi, Elmira; Hosseini Doust , Reza; Rahbar, Mohammad; Rahnamaye Farzami, Marjan (Archives of Medical Laboratory Sciences, 2021)
Background and Aim: One of the most critical concerns in Klebsiella pneumoniae isolated from nosocomial infections is antibiotic resistance due to transferable resistance genes. This study aims to investigate the relationship and role of integrons in the transport of OXA-type genes in the production of carbapenem-resistant isolates. Methods: In this study, 270 isolates of K. pneumoniae were isolated from patients with urinary tract infection symptoms hospitalized at Milad hospital of Tehran during 2017-2018. The biochemical methods confirmed K. pneumoniae isolates. Also, antimicrobial susceptibility testing was performed using an E-test method. Carbapenem-resistant isolates were confirmed using an automated antimicrobial susceptibility testing system (Phenix BD USA). The presence of OXA genes, integron, and its class were determined by PCR method. Results: According to our findings, the most effective antibiotics against uropathogenic K. pneumoniae isolates were piperacillin-tazobactam and meropenem, respectively. Out of the 270 isolates, 27 (10%) were detected as carbapenem-resistant K. pneumoniae isolates. Moreover, 47.2%, 40.1%, 39.2%, and 36.4% of K. pneumoniae isolates were resistant to ceftriaxone, ceftazidime, trimethoprim-sulfamethoxazole, and amoxicillin/clavulanate, respectively. A significant proportion of isolates had class I integron. Meaningful differences in OXA-51, 58, and 24 genes were found in carbapenem-resistant and carbapenem-susceptible K. pneumoniae isolates. No significant relationship was observed between class 1 and 2 integrons and other studied gene determinants of antimicrobial resistance. Conclusion: According to the observed results, OXA-23, OXA-24, OXA-58, and OXA-51-like groups were the most prevalent genes in carbapenem-resistant K. pneumoniae isolates, respectively. Also, 97.9% of carbapenem-susceptible K. pneumoniae isolates had class 1 integron. *Corresponding Author: Dr. Mohammad Rahbar; Email: rahbar@health.gov.ir ORCID: https://orcid.org/0000-0003-2292-3175 Please cite this article as: Pourbaghi E, Hosseini Doust R, Rahbar M, Rahnamaye Farzami M. The Frequency of Integrons and OXA Genes in Uropathogenic Isolates of Klebsiella pneumoniae. Arch Med Lab Sci. 2021;7:1-8 (e23). https://doi.org/10.22037/amls.v7.35178